Representing the Plague in Early Modern England. - Totaro, Rebecca (Routledge Studies in Renaissance Literature and Culture, v. 14, 2010)
A collection that offers readers an encounter with the historical experience of people adapting to a pandemic emergency and the corresponding narrative representation of that crisis, as early modern writers transformed the plague into literature.